Cumulative pre-cooling methods do not enhance cycling performance in tropical climate. - Aurélie Collado; Kévin Rinaldi; Eric Hermand; Olivier Hue (PLoS ONE, 2023)
The main objective of this study was to investigate the effect of mixed cooling techniques (combination of internal and external strategies, with and without menthol) during warm-up for a time trial in tropical climate. Seven heat-acclimatized trained male road cyclists participated in three experimental sessions consisting of 20-min cycling performances on a velodrome track in ecological hot and humid conditions (Guadeloupe, French West Indies; WBGT: 27.64±0.27°C; relative humidity: 76.43±2.19%), preceded by a standardized 30-min warm-up and the ingestion of cold menthol water (1) with a cooling vest soaked in ice water (ICE-VEST), (2) with a cooling vest soaked in ice menthol water (MEN-VEST), and (3) without a vest (NO-VEST). Cycling performance (total distance, distance traveled per 2-min block), physiological parameters (core body temperature recorded, heart rate) and perceptions (exertion, thermal comfort, thermal sensation) were assessed. No between-condition differences were found for physiological parameters, the total covered distance or the distance traveled per 2-min block. However, distance traveled per 2-min decreased with time (p = 0.03), with no difference between conditions, suggesting a variation in pace during the cycling performance trial (e.g., mean±SD: 1321±48.01m at T2; 1308±46.20m at T8, 1284±78.38m at T14, 1309±76.29m at T20). No between-condition differences were found for perception of exertion, thermal comfort and thermal sensation during the warm-up (11.83±3.34; 2.58±1.02; 4.39±0.94, respectively) and the performance (17.85±0.99; 2.70±1.25; 5.20±1.20, respectively) but the pairwise comparisons within condition revealed a significant increase of TS values from T0 (4.57±1.13) to T20 (6.00±0.58) only in NO-VEST condition (p = 0.04). The absence of modification of thermal sensation at the end of the cycling test under the mixed conditions (ICE-VEST and MEN-VEST) suggests a beneficial effect of wearing a cooling vest on thermal sensation although it had no effect on performance.